Rancang Bangun Sistem Monitoring Daya Listrik Cerdas Berbasis Internet of Things Menggunakan Mikrokontroler Arduino Mega Pro 2560 Dan ESP8266-01 - Iksal Rachman; Dede Mukhsin Al Hamdani; Yandi Setia Permadi (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
This intelligent electricity monitoring system aims to overcome the problem of excessive electricity use which results in skyrocketing electricity costs in homes and industries, as well as minimizing the high risk of damage to household equipment due to excessive loads. The intelligent electricity monitoring system is an instrument designed using an Arduino Mega 2560 as a microcontroller, ESP8266-01 as a WiFi module, an I2C LCD as a display, an audio jack socket as a sensor input, a resistor as a voltage divider and a current sensor. YHDC SCT013 as a current measurement tool. From now on, the Arduino Mega 2560 and ESP8266-01 will send monitoring data to users using Internet of Things (IoT) based technology. Notifications will appear on the LCD and on the blynk platform or application screen.